Blood-Testis Barrier and Sperm Delayed in the Cauda Epididymis of the Reproductively Regressed Syrian Hamsters - Jeon, Geon Hyung; Lee, Sung-Ho; Cheon, Yong-Pil; Choi, Donchan (Balsaeng'gwa saengsig, 2021)
The Syrian (golden) hamsters are seasonal breeders whose reproductive functions are active in summer and inactive in winter. In experimental facility mimicking winter climate, short photoperiod (SP) induces gonadal regression. The blood-testis barrier (BTB) of the sexually involuted animals have been reported to be permeable, allowing developing germ cells to be engulfed or sloughed off the epithelium of the seminiferous tubules. The expressions of genes related to the tight junction composing of BTB were investigated in the reproductive active and inactive testes. Claudin-11, occludin, and junctional adhesion molecule (JAM) were definitely expressed in the active testes but not discernably detected in the inactive testes. And spermatozoa (sperm) were observed in the whole lengths of epididymides in the active testes. They were witnessed in only cauda region of the epididymides but not in caput and corpus regions in animals with the inactive testes. The results imply that the disorganization of BTB is associated with the testicular regression. The developing germ cells are swallowed into the Sertoli cells or travel into the lumen, as supported by the presence of the sperm delayed in the last region of the epididymis. These outcomes suggest that both apoptosis and desquamation are the processes that eliminate the germ cells during the regressing stage in the Syrian hamsters.